Safety and Efficacy of Hemospray® in Upper Gastrointestinal Bleeding - Alan Hoi Lun Yau; George Ou; Cherry Galorport; Jack Amar; Brian Bressler; Fergal Donnellan; Hin Hin Ko; Eric Lam; Robert Allan Enns (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Hemospray (Cook Medical, USA) has recently been approved in Canada for the management of nonvariceal upper gastrointestional bleeding (UGIB).